Synthesis of chalcones and its derivative - Maizatul Akmal Ibrahim, 1990-; Farediah Ahmad, supervisor; Fakulti Sains (2011)
Project paper (Sarjana Muda Sains (Kimia Industri)) - Universiti Teknologi Malaysia, 2011